Self‐compensation of DC–DC converters under peak current mode control. Issue 5 (1st March 2017) - El Aroudi, A.; Mandal, K.; Giaouris, D.; Banerjee, S.
Abstract : A new self‐compensation technique is proposed for eliminating subharmonic oscillation and chaotic regimes in dc–dc switching converters under peak current mode control. The proposed method extracts a control signal from the error between the inductor current and a suitable reference and does not require an external signal generator as in the conventional ramp compensation scheme. The analytical expressions of the control domain using Filippov method are obtained. Simulation results show that the proposed technique can be implemented using standard analogue devices and can effectively eliminate subharmonic and chaotic oscillations and can ensure a stable operation for a wide range of the duty ratio.